What influences judgments of physical attractiveness? A comprehensive perspective with implications for mental health. (2nd January 2023) - Hill, Charles T.; Nelson, Shanti Sage; Perlman, Daniel
Abstract: Judgments of physical attractiveness are based on appearance but are influenced by and influence more than just physical features of the face and body (e.g. clothing and personality traits). This is explored in a selective review of previous research, plus new analyses of data from three previously published studies: the Boston Couples Study, the Multiple Identities Questionnaire, and the Intimate Relationships Across Cultures Study, with implications for mental health. Self-ratings of attractiveness are inflated by self-esteem and confidence in self-halo effects. Partner-ratings are inflated by love and relationship satisfaction in partner-halo effects. Positive responses from others influence attractiveness-enhancing cycles, while negative responses influence attractiveness-deprecating cycles, with impacts on well-being. These influences are represented in a comprehensive Attractiveness Halo Model, which identifies Ten Components of Attractiveness that are inter-related, including physical, emotional, sexual, sensory, intellectual, behavioural, observer, situation, reciprocity, and time. Aspects of the model are supported by analyses of the three studies, generalising comprehensive attractiveness halo effects across time, identities, cultures, and relationship types.